The black Jesus: Racism and redemption in John Updike's Rabbit Redux. - Boswell, Marshall (Contemporary Literature)
Presents information on racism and redemption as it relates to the book `Rabbit Redux,' by John Updike. Information on the contents of the book; How Rabbit treated the race issue in the book; Identification of the individual who influences Updike's work.